Crowd Modelling and Navigation in Unity3D Game Engine: Crowd Modelling and Navigation in Unity3D Game Engine - Mochammad Fachri; Avip Kurniawan; Ali Khumaidi (Jurnal Mantik, 2020)
In the curret era of building construction and development, it is very difficult to foresee the evacuation point of a building if disaster occure, especially for huge and tall buildings. For that purpose we make crowd modeling on the Unity3D game engine. We try to build a concept using evacuation scenarios in the Krisnadwipayana University, Faculty of Engineering building. By utilizing crowd modeling using Unity3D game engine, we will put all crowd agents together at the virtual environment of the target building at maximum density. In this study we using the prototype method to build the virtual area/building, and mapping the movement of the crowds in order to calculate the movement to be carried out in a form of visual crowds movement. The results of research conducted show that the final prototype that was made can accept 3D building models using Sketchup. From the data that has been made through the prototype there are 4498 agents who exit through the main door and 2068 agents use the back door of the target building, with the time needed to evacuate for 2 minutes and 16 seconds. The conclusion of this research is that it is able to present a crowd modeling form with integrated navigation on the game engine, and by using Unity3D for crowd modeling, it can help various groups that require testing in an area.